Antimicrobial properties of various solvents combinations for phytochemical fraction derived from Uncaria gambier extract against Enterococcus faecalis ATCC 29212 - Sovira, Gita Dwi Jiwanda; Satari, Mieke Hemiawati; Mariam, Marry Siti (Universitas Padjadjaran, 2021)
Introduction: Enterococcus faecalis is often found in root canal infections and can cause failure in root canal treatment. Uncaria gambier is an herbal medicine that is known to be rich in polyphenol compounds that have antibacterial properties. Because of the polyphenol content and antibacterial properties of Uncaria gambier, it can be an alternative as an antibacterial solution for root canal treatment. The purpose of this study is to analyze the antimicrobial of various solvents combinations for phytochemical fraction derived from Uncaria gambier extract against Enterococcus faecalis (ATCC 29212). Methods: This study is descriptive explorative research Uncaria gambier was extracted using a combination of three different fractions, ethyl acetate-water, hexane-water and hexane-ethyl acetate. We determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) against Enterococcus faecalis (ATCC 29212) using the serial microdilution method and by add test samples to the Mueller Hinton agar medium from each fraction Results: Combination Ethyl Acetate-water has MIC value at 0.195 mg/ml, combination Hexane-water at 0.049 mg/ml and combination Hexane- Ethyl Acetate have the MIC value at 1.563 mg/ml. The MBC value in combination Ethyl Acetate-water at 25 mg/ml, combination Hexane-Ethyl Acetat and Hexane-water MBC value at 50 mg/ml and 100 mg/ml. Based on optical density measurement using ELISA Reader and bacterial growth on the media used, the fraction combinations increase the antibacterial effect of Uncaria gambier against E. faecalis ATCC 29212. Conclusion: The combination of various Uncaria gambier solvents has been shown to inhibit and kill E. faecalis (ATCC 29212). The combination of Ethyl Acetate-water fraction is the best combination to against E. faecalis (ATCC 29212). It means that the combination of various Uncaria gambier solvents can be developed as alternative root canal irrigation.